2020
DOI: 10.1089/aut.2019.0069
|View full text |Cite
|
Sign up to set email alerts
|

Autism Identity and the “Lost Generation”: Structural Validation of the Autism Spectrum Identity Scale and Comparison of Diagnosed and Self-Diagnosed Adults on the Autism Spectrum

Abstract: Background: A population segment of autistic adults are underidentified due, in part, to historic changes in criteria for diagnosing autism and diagnostic biases related to gender, socioeconomic status, and other individual characteristics such as intellectual functioning. Some of these individuals, described as the ''lost generation,'' may choose to self-diagnose. Although little is known about this population, it is possible that they share similar self-conceptualizations or internalized stigma as their diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Study 1 suggested that autistic adults experience lower QoL than TDs, as has been found by other studies (McDonald, 2020 ; van Heijst & Geurts, 2015 ). However, in contrast to other research (van Heijst & Geurts, 2015 ), autistic adults in our study were found to have a different developmental trajectory than TDs regarding age and its relation to QoL outcomes.…”
Section: Study 1 Discussionsupporting
confidence: 65%
“…Study 1 suggested that autistic adults experience lower QoL than TDs, as has been found by other studies (McDonald, 2020 ; van Heijst & Geurts, 2015 ). However, in contrast to other research (van Heijst & Geurts, 2015 ), autistic adults in our study were found to have a different developmental trajectory than TDs regarding age and its relation to QoL outcomes.…”
Section: Study 1 Discussionsupporting
confidence: 65%
“…Evidence has suggested that following a diagnosis of ASD, anxiety reduces in autistic adults, it is also possible that anxiety is related to camouflaging practises often seen in self-diagnosed individuals ( 24 ). This finding could also reflect a lack of healthcare support provided to autistic individuals who have not received a diagnosis leading to higher anxiety outcomes ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, during the Time 1 survey we did ask participants to provide information on their diagnosis (e.g., age of diagnosis, professional who gave the diagnosis and month and year of the diagnosis) to potentially limit this issue. A recent study by McDonald ( 25 ) provided a comparison between autistic adults that are self-diagnosed vs. diagnosed by a HCP, the study found the inclusion of self-reported autistic adults in online surveys likely represents the “lost generation” of autistic adults, such as older females. In our sample there are three times more females than males included aged between 18 and 65 years old.…”
Section: Limitationsmentioning
confidence: 99%
“…Further, participants who self-reported their autism diagnosis were also included in the sample. That said, McDonald [ 44 ] compared autistic adults self-diagnosed to autistic adults diagnosed by a HCP and found the inclusion of self-reported autistic adults in online surveys likely represents the “lost generation” of autistic adults, such as older females. In the present sample, there were twice as many females than males, aged between 18 and 73 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited for an online survey, between November 2019 to February 2020, via social media and autism support groups. All adults that identified as an autistic adult were included in our sample to allow access to a more diverse population and reduce barriers related to accessing an autism diagnoses in adulthood [ 43 , 44 ]. Of the 837 UK participants that responded to the online Qualtrics XM survey, 58.90% fully completed the survey ( n = 493 final sample).…”
Section: Methodsmentioning
confidence: 99%